Among‐lake variation in vertical distribution of invasive, bloom‐forming algal species Gonyostomum semen (Raphidophyceae) in stratified humic lakes of eastern Poland. Issue 4 (22nd October 2013) - Pęczuła, Wojciech; Mencfel, Radosław; Kowalczyk‐Pecka, Danuta
<x xml:space="preserve">Abstract</x> In recent years, there has been an increasing interest in the ecology of algal species Gonyostomum semen (Ehr.) Diesing, as it is often referred as an invasive species and a climate change indicator. Like many other flagellates, the species has the ability to active swimming, therefore it is often found unevenly distributed in the water column. Although there are several studies focused on the species vertical distribution (VD) and its diurnal changes, there is no general agreement about the causes and mechanisms of the phenomenon. In this paper, we analyzed G. semen VD in three stratified humic lakes in the new area of its spread in Central Europe, aiming to determine the common pattern of this phenomenon as well as to search any relationship with chemical and biotic factors. The results of this investigation showed that VD of the alga during the day varied among three lakes and that Gonyostomum migrated upward in the morning and downward in the afternoon, but it could stay in deep, anoxic and dark layers through most of the diurnal cycle. The analysis of chemical factors revealed that phosphate retrieval from deeper layers is probably not a key driver of the alga uneven VD and its migrations. Diurnal observations showed that three dominating zooplankton species (Asplanchna priodonta, Ceriodaphnia quadrangula, and Eudiaptomus graciloides) changed their vertical position in parallel to Gonyostomum. We have suggested in conclusions that the pattern of G. semen VD in temperate stratified lakes is not universal, but rather depends on particular lake conditions, including phosphate content and light climate. Since the zooplankton VD could play a regulating role in the alga behavior, further research in this field would be of great help in understanding this invasive alga ecology.